BIOCHEMICAL STUDIES ON BLOOD METABOLITES IN KETOTIC CROSSBRED COWS FOLLOWING TREATMENT - Biswal, S; Nayak , D C; Parida , G S; Sardar , K K (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The blood metabolic test was carried out in six selected dairy herds located inside Bhubaneswar and maintained under similar feeding, housing and managerial practice. Forage provided was mainly paddy straw. 48 cows between 30-120th day of lactation was included in the present study. For normal metabolic profile, 18 crossbred Jersey cows showing ketotic symptoms were selected from the same herd. The plasma glucose level in three groups showed to be significantly (P <0.05) different in group I and highly significant (P <0.01) in group II and III before and 7th day following treatment. A rise in serum Ca and Pi level in all the groups was also recorded but it was not significant.